The use of folktale songs in the development of character among E.C.D “B” learners at Gresham primary school in Zvishavane - Moyo, Babra (Midlands State University, 2018)
The purpose of this study was to develop character among E.C.D ‘B’ learners at Gresham Primary School. This was achieved through an action research where folktale songs were taught as a way of developing the character of E.C.D ‘B’ learners at the school. The population comprised of all E.C.D teachers and learners at Gresham School whereas the sample consisted of four E.C.D teachers and thirty three E.C.D ‘B’ learners. Data was presented both in the qualitative and quantitative forms. Pre-test and post test results were presented in the form of pie charts and graphs while lesson plans and their discussions were presented in the form of narratives. Findings indicated that some improvements were noted in the learners’ behaviour after some folktale songs were taught and discussed in an effort to bring out some moral values in them. It was noted that many learners were no longer involved in other forms of unacceptable behaviours like cheating, stealing or lying. This was a clear indication that folktale songs have a role to play towards moulding the character of E.C.D ‘B’ learners though it is a long term process. From the findings, I therefore recommend that folktale songs be collected and transcribed for use in schools. School based workshops should be conducted as a way of equipping teachers on how they can use folktale songs towards the development of the learners’ character.